Adherence to treatment recommendations of patients with chronic non-communicable respiratory diseases – a narrative review: Adherence in asthma and COPD - Homętowska, Henryka (Journal of Education, Health and Sport, 2023)
Despite modern therapeutic solutions, patients with chronic obstructive pulmonary disease (COPD) and asthma do not achieve therapeutic benefits due to emerging obstacles to compliance. This review aimed to present and analyze the results of available studies evaluating the influence of sociodemographic, clinical, and psychosocial factors on the level of adherence of patients with COPD and asthma. This narrative review was based on papers indexed in the following databases: PubMed, MEDLINE, CINAHL, Web of Science, and Scopus. The analyzed studies showed that the adherence level of patients with COPD and asthma is unsatisfactory, ranging from 23.6 to 80%. The main factors increasing the level of adherence of COPD patients mentioned in the analyzed studies were: unemployment, taking LAMA, not smoking cigarettes, belief that medication is necessary, higher education, use of multi-dose DPI and MDI inhalers, a greater sense of self-efficacy, and longer duration of disease. Independent determinants of good adherence of patients with asthma were better quality of life, high level of disease control, treatment with ICS + LABA or FF/UMEC/VI, good knowledge about asthma, and positive attitude towards the disease. According to available studies, determinants lowering adherence among patients with COPD were overweight or obesity, depression, poor quality of life, belief that treatment is harmful, frequent hospitalizations, lack of knowledge about the disease and treatment, sleep disorders, and use of ICS, LABA/ICS. Patients with asthma who received infrequent functional support consumed alcohol and were convinced of the harm and lack of need for treatment were non-adherent. In addition, an association was shown between high levels of adherence and a reduction in ED visits and hospitalizations in asthma and COPD patients.